The interactive effects of socialization tactics and work locus of control on newcomer work adjustment, job embeddedness, and voluntary turnover - Peltokorpi, Vesa; Feng, Jie; Pustovit, Sasha; Allen, David G; Rubenstein, Alex L (Human relations (New York), 2022)
Previous research has tended to focus on general best practices for onboarding organizational newcomers. In this study, we shift the conversation to instead address the question: for whom are certain socialization tactics more or less beneficial? Whereas institutionalized socialization tactics provide considerable structure intended to reduce uncertainty and help newcomers adjust, less is known about whether and how individual psychological differences cause some newcomers to react differently to the same socialization tactics. To examine the interplay between organizational socialization efforts and newcomer individual differences, we hypothesize that newcomers’ work locus of control moderates the relationship between socialization tactics and voluntary turnover. We also examine the indirect role of newcomer work adjustment—role clarity, work mastery, social integration—and job embeddedness in transmitting the interaction between socialization tactics and work locus of control to turnover. Data collected from 676 newcomers at four time points over 12 months in various organizations provided general support for our hypotheses: newcomers with an external work locus of control showed higher social integration and embeddedness and lower turnover under institutionalized socialization tactics, but lower social integration and embeddedness and higher turnover under individualized tactics. Their turnover was also reduced (about nine times) from individualized to institutionalized tactics. In contrast, newcomers with an internal work locus of control were less influenced by either socialization tactic approach in terms of their social integration, embeddedness, or turnover.